Recent Advances of Drugs in COPD (International Journal of Food and Nutritional Sciences, 2022)
Multiple etiologies are linked to the condition known as “chronic obstructive pulmonary disease (COPD)”. It is the leading global cause of morbidity and mortality. Chronic bronchitis, emphysema, and airway remodelling are the hallmarks of chronic obstructive pulmonary disease (COPD), a lung condition that causes structural changes in both small and large airways as a result of subepithelial fibrosis, increased smooth muscle mass of the airways, neovascularization, and glandular hypertrophy. In every country in the world, its prevalence is rising daily. Few effective medications are currently available, but none of them can stop the disease from progressing or address all of its defining symptoms.This study summarises some of the most recent developments because existing treatments only address a subset of symptoms and do not work to reverse the disease's defining characteristics.